Beneficial synergistic effect on bio-oil production from co-liquefaction of sewage sludge and lignocellulosic biomass. (March 2018) - Leng, Lijian; Li, Jun; Yuan, Xingzhong; Li, Jingjing; Han, Pei; Hong, Yuchun; Wei, Feng; Zhou, Wenguang
Graphical abstract: Highlights: Co-liquefaction of municipal sewage sludge and biomass enhanced bio-oil yield. Co-liquefaction improved the quality of bio-oil. Co-liquefaction reduced the content of heavy fraction in bio-oil. Abstract: Co-liquefaction of municipal sewage sludge (MSS) and lignocellulosic biomass such as rice straw or wood sawdust at different mixing ratios and the characterization of the obtained bio-oil and bio-char were investigated. Synergistic effects were found during co-processing of MSS with biomass for production of bio-oil with higher yield and better fuel properties than those from individual feedstock. The co-liquefaction of MSS/rice straw (4/4, wt) increased the bio-oil yield from 22.74% (bio-oil yield from liquefaction of MSS individually) or 23.67% (rice straw) to 32.45%. Comparable increase on bio-oil yield was also observed for MSS/wood sawdust mixtures (2/6, wt). The bio-oils produced from MSS/biomass mixtures were mainly composed of esters and phenols with lower boiling points (degradation temperatures) than those from individual feedstock (identified with higher heavy bio-oil fractions). These synergistic effects were probably resulted from the interactions between the intermittent products of MSS and those of biomass during processing.